Diseño arquitectónico de un proyecto de vivienda para estudiantes de provincia de la ULVR - Anai Branda, Genesse Julieth (2024)
The project of an architectural design for student housing of the Universidad Laica Vicente Rocafuerte (ULVR) of the province, located in the city of Guayaquil, addresses the problem of the lack of adequate accommodation for students from other places. This lack involves long and tiring journeys from their places of origin to the university. The fundamental purpose of the project is to establish an innovative and sustainable environment that promotes the well-being and comfort of the residents. The proposal is based on the use of several materials for the construction of the house such as a metal structure that guarantees resistance and durability, along with the use of ecological concrete to minimize the environmental impact, also the choice of other types of materials that not only seek to optimize energy efficiency and allow adequate natural lighting, but also the use of natural lighting. it also reflects a commitment to sustainability in construction. The spatial distribution of the project focuses on maximizing the functionality and comfort of the spaces, prioritizing common areas to encourage interaction between residents and create a community environment. In addition, design elements that promote safety and well-being are incorporated, such as access control systems and green areas, i.e., the design of housing for students of the ULVR of the province seeks to address the need for adequate accommodation for this population, through the creation of a comfortable, innovative, sustainable and functional space that fosters a healthy standard of living in its university residents.